Effect of 15 consecutive HIIT sessions on the redox State in Wistar rats - Josimar Camacho Rodrigues; Roas de Araújo Costa; Felipe José Aidar; Raphael Fabrício de Souza; Ciro José Brito; Jymmys Lopes dos Santos; Lucio Marques Vieira-Souza (Desafio Singular, 2023)
High-intensity interval training (HIIT) can induce oxidative stress. The main aim of this study was to evaluate the effect of 15 sessions of a HIIT protocol in Wistar rats on oxidative damage markers in different tissues (blood, muscle, liver and heart). Thus, animals weighing 250-300g were used and randomly divided into 2 groups (n=10): Control (CG) and animals submitted to HIIT (TG) through a swimming protocol. The results showed that HIIT increased the production of malondialdehyde (MDA) in TG animals: serum (306.75%), gastrocnemius muscle (259.2%), liver (452.6%) and heart (215%), while the concentration of sulfhydryl groups decreased: serum (40%), gastrocnemius muscle (44.7%), liver (44.6%) and heart (47.2%). Thus, it could be concluded that 15 HIIT sessions altered the redox state of Wistar rats due to increased oxidative damage markers in the analysed tissues.